1987
DOI: 10.1007/bf01907228
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the regional distribution and response to ischaemia of adenosine-regulating enzymes in the heart

Abstract: The activities of the adenosine-generating enzyme 5'-nucleotidase and the adenosine-degrading enzyme adenosine deaminase were determined for four regions of rat hearts prior to and following 10-60 min of ischaemia. Whereas adenosine deaminase was uniformly active throughout the heart, 5'-nucleotidase was twice as active in atrial than in ventricular myocardium, and more active in the right than in the left ventricles in normoxic tissues. In isolated heart preparations normoxic perfusion decreased adenosine dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…All procedures were performed at þ 4 C. The determinations listed below were made on the samples according to the cited references at the Biochemistry Laboratory of Turgut Ozal Medical Center using products by Sigma. MDA 19 and NO (nitrate was measured as an index of NO production) 20 levels were determined in the homogenate, ADA, 21 XO, 22 CAT, 23 GSH-Px 24 activity in the supernatant and SOD activity in the extracted samples 25 according to the methods described elsewhere. Protein measurements were made at all stages by the method described by Lowry.…”
Section: Methodsmentioning
confidence: 99%
“…All procedures were performed at þ 4 C. The determinations listed below were made on the samples according to the cited references at the Biochemistry Laboratory of Turgut Ozal Medical Center using products by Sigma. MDA 19 and NO (nitrate was measured as an index of NO production) 20 levels were determined in the homogenate, ADA, 21 XO, 22 CAT, 23 GSH-Px 24 activity in the supernatant and SOD activity in the extracted samples 25 according to the methods described elsewhere. Protein measurements were made at all stages by the method described by Lowry.…”
Section: Methodsmentioning
confidence: 99%
“…15 One unit of activity was de®ned as 1 mmol of uric acid formed per minute at 37 C, pH 7.5, and expressed in IU ml À 1 . ADA activity was determined by a method described elsewhere 16 and enzyme activity was expressed as Ul À 1 . Since nitrite (NO 2 À ) and nitrate (NO 3 À ) levels can be used to estimate NO production, we measured the concentrations of these stable NO oxidative metabolites for determining the NO levels.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Deusscn et al (5) have reported that S-adenosylhomocysteine hydrolase may have an important role in the regulation of the free cytosolic adenosine concentration. Recently, Choong and Humprey (6) have reported that 5'N and ADA enzyme activities exhibit regional differences in their distribution in the rat heart. In previous work we showed that these two enzyme activities are not uniformly distributed across the rat left ventricle wall (7) and that the profiles of their distribution across the heart wall are strongly influenced by growth and aging (8).…”
Section: Introductionmentioning
confidence: 99%